Halochromic properties of carotenoid-based films for smart food packaging - Mussagy, Cassamo U.; Oliveira, Grazielle; Ahmad, Mushtaq; Mustafa, Ahmad; Herculano, Rondinelli D. [UNESP]; Farias, Fabiane O. (Elsevier, 2024)
Carotenoids are fat-soluble natural pigments with potent antioxidant and antibacterial properties, and their colors are sensitive to environmental pH changes (halochromic properties). Currently, natural carotenoids are utilized in the preparation of active packaging films, drawing significant attention in the field of food engineering for their potential application in smart packaging films. The use of carotenoids-based active films has shown promise in prolonging shelf life, but their application as pH-sensitive pigments in smart packaging for monitoring food freshness remains less established due to the several drawbacks (i.e., visual changes and others) discussed in this work. This critical review primarily summarizes the most used smart packaging materials, the halochromic properties of carotenoids and other pigments, and the applications of carotenoids-based films/bioplastics as pH-sensitive smart packaging for monitoring food freshness. Finally, we present to the readers our expert overview of the advantages and disadvantages associated with these natural pigments in the packaging sector.
Keywords: Carotenoid; Food; Freshness; PH indicator; Shelf-life; Smart packaging